Treatment approaches for EGFR-inhibitor-resistant patients with non-small-cell lung cancer. Issue 9 (September 2015) - Tan, Chee-Seng; Gilligan, David; Pacey, Simon
Summary: Discovery of activating mutations in EGFR and their use as predictive biomarkers to tailor patient therapy with EGFR tyrosine kinase inhibitors (TKIs) has revolutionised treatment of patients with advanced EGFR -mutant non-small-cell lung cancer (NSCLC). At present, first-line treatment with EGFR TKIs (gefitinib, erlotinib, and afatinib) has been approved for patients harbouring exon 19 deletions or exon 21 (Leu858Arg) substitution EGFR mutations. These agents improve response rates, time to progression, and overall survival. Unfortunately, patients develop resistance, limiting patient benefit and posing a challenge to oncologists. Optimum treatment after progression is not clearly defined. A more detailed understanding of the biology of EGFR -mutant NSCLC and the mechanisms of resistance to targeted therapy mean that an era of treatment approaches based on rationally developed drugs or therapeutic strategies has begun. Combination approaches—eg, dual EGFR blockade—to overcome resistance have been trialled and seem to be promising but are potentially limited by toxicity. Third-generation EGFR -mutant-selective TKIs, such as AZD9291 or rociletininb, which target Thr790Met-mutant tumours, the most common mechanism of EGFR TKI resistance, have entered clinical trials, and exciting, albeit preliminary, efficacy data have been reported. In this Review, we summarise the scientific literature and evidence on therapy options after EGFR TKI treatment for patients with NSCLC, aiming to provide a guide to oncologists, and consider how to maximise therapeutic advances in outcomes in this rapidly advancing area.